An Eco-theological Model for Strengthening Environmental Resilience in Pasir Village, Sumenep Regency, Madura - Hakiki, Ach; Rosyad, Rifki; Huriani, Yeni (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
The coastal environmental crisis is a serious problem that demands a multidimensional approach that is not only technical, but also touches on the spiritual and socio-cultural aspects of the community. This study aims to formulate a Madurese contextual ecotheology model as a strategy to strengthen coastal environmental resilience, with a case study in Kampung Pasir, Sumenep Regency. This study uses a qualitative approach with ethnographic and phenomenological methods, through participatory observation, in-depth interviews, and documentation studies of the socio-religious life of coastal communities. Data analysis was carried out with a thematic and interpretative approach to identify the relationship between religious values ​​and ecological practices of the community. The results of the study indicate that theological values ​​such as the concept of caliph, trust, prohibition fasad(damage), as well as the principles of blessing and harmony have shaped the environmental ethics that live within the community. These values ​​are internalized through the role of religious leaders, social interaction patterns, religious traditions, and mutual cooperation mechanisms that regulate human relations with nature. This study also formulates a Madurese contextual ecotheology model that encompasses five main dimensions: theological, socio-communal, environmental education, ecological practices, and local policies. This model offers an integrative framework that connects faith, local culture, and environmental conservation strategies in a sustainable manner. This study concludes that the Madurese coastal context-based ecotheology approach has strategic potential as a guideline for strengthening environmental resilience rooted in spirituality and local wisdom, and is relevant for the development of community-based environmental policies in coastal areas of Indonesia.